Croton mubango Müll. Arg.: Its Botany, Ethnomedicinal Uses and Pharmacological Properties - Alfred Maroyi (Journal of Pharmacy and Nutrition Sciences, 2018)
Croton mubango is widely used as traditional medicine in tropical Africa. The potential of C. mubango as traditional medicine, its botany, chemical and pharmacological activities are reviewed. The literature relevant to the study was obtained from scientific databases such as BioMed Central (BMC), Web of Science, Google Scholar, Scopus, Science Direct, PubMed, Springerlink and Scielo. Other supplementary literature such as books, book chapters, theses, conference papers and other scientific publications were obtained from the University of Fort Hare Library and dissertation search engines such as EThOS, OATD, ProQuest and Open-thesis. Literature search revealed that the bark, fruits, leaves and roots of C. mubango are commonly used as traditional medicines for abdominal pain, diarrhoea, dysentery, fever, hernia, intestinal worms, malaria, rheumatism, toothache, tuberculosis and as purgative. Phytochemical compounds isolated from C. mubango include alkaloids, flavonoids, reducing sugars, saponins, steroids, tannins, terpenes and triterpenes. Pharmacological studies on C. mubango indicate that the species has in vitro and in vivo antiplasmodial activities. Several medicinal applications and therapeutic potentials of C. mubango have been demonstrated in this study although the majority of them still need pharmacological validation.